Serum metabolomics reveal the mechanisms by which fermented brewer’s spent grains promote intestinal development in white-feathered broilers - Li, Yuanfeng; Meng, Zhiheng; Wang, Yiyuan (Frontiers in Veterinary Science, 2025)
This study aimed to investigate the effects of wet-fermented brewer’s grains (WFBGs) on gut development and serum metabolism in white-feathered broilers. A total of 192 one-day-old male broilers (initial body weight: 36.46 ± 0.93 g) were randomly assigned to two treatment groups: the control group (0% WFBGs) and the experimental group (20% WFBG inclusion), with 6 replicates of 16 birds per replicate. The results of intestinal morphological parameters, quantified using ImageJ software after hematoxylin–eosin (HE) staining, showed that compared with the control group, broilers fed a diet supplemented with 20% WFBGs had significantly improved duodenal development. Specifically, the duodenal villus height (VH) increased by 10.2% (p < 0.05), and the villus height-to-crypt depth ratio (VH/CD) increased by 27.2% (p < 0.05)—both indicators reflecting enhanced duodenal development. Through untargeted metabolomics analysis for screening differentially expressed metabolites (DEMs) from serum samples, 211 DEMs were identified, including 98 upregulated DEMs and 113 downregulated DEMs in the WFBG group. KEGG pathway enrichment analysis revealed that these DEMs were significantly associated with key metabolic processes, including linoleic metabolic pathways, linoleic acid metabolism, phenylalanine metabolism, and other relevant pathways. Specifically, key DEMs involved in amino acid metabolism included significantly increased phenylalanine levels and decreased 4-HPA and 3-HPA levels (p < 0.05). In conclusion, the inclusion of 20% WFBGs in the diet of white-feathered broilers significantly promoted intestinal development. These favorable outcomes are tied to modified serum metabolic profiles and shifts in lipid and amino acid metabolism in broilers, underscoring WFBG’s significance for boosting broiler intestinal development while also adding to the theoretical framework for poultry by-product-based feeds.